PREVENTION OF VENOUS THROMBOEMBOLIC COMPLICATIONS IN REPLACEMENT ARTHROPLASTY PERFORMANCE IN PATIENTS WITH ASSOCIATED CHRONIC DISEASES OF LOWER EXTREMITIES VEINS - V. V. Sabel’Nikov; O. V. Zlobin; A. I. Prokopets; A. O. Denisov; A. Yu. Avetyan (Вестник хирургии имени И.И. Грекова, 2016)
A number of patients with problems of major joints increases every year. These patients need the replacement arthroplasty. The rate of thrombotic complications rises in given category of patients simultaneously with the increase of the number of performed operations. There weren’t well-defined instructions of management of the patients with associated chronic vein diseases at the preparation period for arthroplasty performance in spite of the presence of clinical recommendations for prevention of thromboembolic complications. The authors analyzed the experience of management of such patients and presented these data for doctors from polyclinic and hospitals in order to apply the common treatment strategy.